2022
DOI: 10.1088/1741-4326/ac4db8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha particles on the CTEM driven zonal flow in deuterium–tritium tokamak plasmas

Abstract: The effects of fusion-born alpha (α) particles on zonal flow (ZF) driven by collisionless trapped electron mode (CTEM) turbulence are analytically investigated, using gyrokinetic and bounce kinetic theories in the deuterium-tritium (D-T) tokamak plasmas. It is found that ZF growth rate is increased by α particles because of the reduction of polarization shielding as well as enhancement of CTEM instability. The results of this paper are qualitatively consistent with the enhancement of the level of residual ZF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Unless otherwise stated, we will take the following normalized parameters from the cyclone DIII-D base case as in the gyrokinetic simulations [56,57], but artificially exchange the magnitudes of electron density gradient and electron temperature gradient as in [35]. The mixing ratio of D-T ions is 1:1, ε 0 = 0.1, q = 1.4, ŝ = 0.8, R/L ne = 6.9, R/L Te = 2.2, Leα = 2, LeHe = 1, and both the temperature gradient of D-T ions and helium ash are artificially set as R/L T j = 0.1 ( j = D, T, He) to avoid ITG instability [29,35,58]. Similar artificial treatment by setting R/L T j = 0 has also been used in [51,59,60], and it has been shown that the wavenumber spectrum of the linear growth rate of both trapped electron mode (TEM) instability [61] and CTEM driven zonal flow (ZF) [51] would not been qualitatively changed by slightly increasing R/L T j .…”
Section: Effects Of α Particles On the Parametric Dependence Of Heliu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise stated, we will take the following normalized parameters from the cyclone DIII-D base case as in the gyrokinetic simulations [56,57], but artificially exchange the magnitudes of electron density gradient and electron temperature gradient as in [35]. The mixing ratio of D-T ions is 1:1, ε 0 = 0.1, q = 1.4, ŝ = 0.8, R/L ne = 6.9, R/L Te = 2.2, Leα = 2, LeHe = 1, and both the temperature gradient of D-T ions and helium ash are artificially set as R/L T j = 0.1 ( j = D, T, He) to avoid ITG instability [29,35,58]. Similar artificial treatment by setting R/L T j = 0 has also been used in [51,59,60], and it has been shown that the wavenumber spectrum of the linear growth rate of both trapped electron mode (TEM) instability [61] and CTEM driven zonal flow (ZF) [51] would not been qualitatively changed by slightly increasing R/L T j .…”
Section: Effects Of α Particles On the Parametric Dependence Of Heliu...mentioning
confidence: 99%
“…α particles and/or electron cyclotron resonance heating (ECRH) mainly heat electrons, and thus one scan of T e is under fixed T i = 10 keV. The other case is raising T i and T e simultaneously under T i = T e , which is widely used for studying the effects of energetic particles on drift wave and ZF [33,58,67].…”
Section: The Effects Of Electron Parameters: T E and R/l Nementioning
confidence: 99%